Pharmaceutical Formulation of Garlic and Turmeric Dried Crude Extract and Their Synergistic Antifungal Activity and Safety: Pharmaceutical formulation of garlic and turmeric dried crude extract - Kazi, Hamid Ali; Channa, Tahseen; Unar, Ayaz Ali; Unar, Khalida; Sabzoi, Waqar; Perveen, Shazia; Mangi, Altaf Ali; Ahmer, Arslan (Iranian Journal of Pharmaceutical Sciences, 2018)
Candidiasis is a fungal infection caused by Candida albicans. Allium sativum (garlic) and Curcuma longa (turmeric) have been used as antifungal agents. The main aim of this study was to identify the effectiveness of these natural products towards C. albicans and on their pharmacological and toxicity aspects. Thus, agar disc diffusion method was used to study the antifungal activity of the ethanolic extracts. Fluconazole served as the positive control while solvent (ethanol) served as the negative control. Minimum inhibitory concentration (MIC) of the plant extracts were tested by using two fold agar dilution method at concentrations ranging from 0.390g/L to 100g/L. As delivery agents, cream and gel formulations demonstrated good stability test results. Furthermore, both plants showed synergistic effects. Active compound of garlic and turmeric which is allicin and curcumin were observed through Thin Layer Chromatography (TLC). Moreover, all the formulation resulted in optimum MIC at pH 5.5 and temperature 25.5ºC. Toxicity test using Brine Shrimp Lethality Test (BSLT) showed that ethanolic extracts of both plants displayed LC50 values at 77.93μg/mL and 31.97μg/mL. Whereas, LC50 value of synergistic experiments of extract was 10.77μg/mL. Besides, synergistic cream formulation was most potent against brine shrimp larvae compared to others with LC50 value of 5.35μg/mL. Synergistic experiment using gel formulation also showed potency against brine shrimp larvae with LC50 value of 3.58μg/mL. As a conclusion, both plant extracts and preparations showed significant effectiveness against C. albicans and potency on shrimps.